Assessment of the oral health literacy and oral health behaviors among nurses in China: a cross-sectional study - Ran An; Wen-feng Chen; Siyu Li; Zitong Wu; Meizi Liu; Muhammad Sohaib (BMC Oral Health, 2022)
Abstract Purpose Oral health is important for general health; nurses are expected to possess good oral health awareness and work together for public oral health promotion. The purpose of this study is to investigate oral health literacy (OHL)and oral health behaviors of nurses, and explore the association between oral health literacy with demographic variables and oral health behaviors. Methods A cross-sectional study in a tertiary hospital was conducted using a short-form Health Literacy in Dentistry-14 (HeLD-14) and a 16-items oral health behaviors questionnaire. Information about the subjects’ demographic details including age, gender, place of residence, marital status, marital status, education level, monthly household income, working experience, etc. were collected. Independent sample t- test, One- way ANOVA, and multivariable regression were used to identify the association of oral health literacy with demographic variables and oral health behaviors. Results A total number of 317 nursing nurses participated in the survey, with a mean OHL score of 36.72, SD10.531, 21.8% were categorized as good, 34.1% medium and 44.2% poor oral health literacy; monthly household income, self-rated oral health, brushing time, use of fluoride toothpaste, and regular oral examination were signficantly associated with OHL scores. Conclusion The overall oral health literacy of the nurse population is at a moderate to low level. These findings may help to map and design an oral health education intervention to improve oral health literacy amongst nurses, especially nurses with low monthly household income and poor self-assessed oral health status. Nursing administrators and nursing educators should pay more attention to the oral health status of the nurse population.